Peran Kepuasan Kerja dalam Memediasi Pengaruh Iklim Organisasi dan Job Insecurity terhadap Turnover Intention - Zainur Ihsan; Wulan Purnama Sari; Kiki Pradana Putra (Value : Jurnal Manajemen dan Akuntansi, 2026)
This study examines the impact of organizational climate and job insecurity on turnover intention, focusing on the mediating role of job satisfaction among 38 employees at SMK Muhammadiyah Sintang. Using an explanatory quantitative design with saturated sampling, data from Likert-scale questionnaires were analyzed via PLS-SEM using SmartPLS. The results demonstrate that a supportive organizational climate significantly boosts job satisfaction and reduces turnover intention. Conversely, job insecurity decreases satisfaction and drives the urge to resign. Furthermore, job satisfaction effectively lowers turnover intention and acts as a partial mediator between these variables. Ultimately, fostering a positive work environment and minimizing job insecurity are essential to enhance staff satisfaction and retain valuable employees in educational institutions.